2013
DOI: 10.7314/apjcp.2013.14.9.5171
|View full text |Cite
|
Sign up to set email alerts
|

No Association of XRCC1 and CLPTM1L Polymorphisms with Non-small Cell Lung Cancer in a Non-Smoking Han Chinese Population

Abstract: Background: This study aimed to explore potential associations between single nucleotide polymorphisms (SNPs) of the x-ray repair cross-complementing group 1 (XRCC1) and cleft lip and palate transmembrane protein 1-like (CLPTM1L) and non-small cell lung cancer (NSCLC) susceptibility in non-smoker Chinese patients. Methods: A total of 200 NSCLC patients and 200 healthy controls with matched age and gender were recruited for genotyping of XRCC1 SNPs (rs2256507 and rs1001581) and CLPTM1L SNPs (rs401681 and rs4975… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
2
5
1
Order By: Relevance
“…However, it was recently reported that rs401681 CT genotype was showed protective effect on lung cancer risk in Asian populations (Bae et al, 2012;Chen et al, 2012). In contrast to above studies, Zienolddiny et al (2009) and Sun et al (2013) did not find any significant association between rs401681 and lung cancer. Base on our research, the rs401681 polymorphism may not affect individual susceptibility to lung cancer.…”
Section: Discussioncontrasting
confidence: 57%
“…However, it was recently reported that rs401681 CT genotype was showed protective effect on lung cancer risk in Asian populations (Bae et al, 2012;Chen et al, 2012). In contrast to above studies, Zienolddiny et al (2009) and Sun et al (2013) did not find any significant association between rs401681 and lung cancer. Base on our research, the rs401681 polymorphism may not affect individual susceptibility to lung cancer.…”
Section: Discussioncontrasting
confidence: 57%
“…In present study, no significant independent association of XRCC1 and XPD polymorphisms for LC was observed. These findings are concordant with some of the previous reports over different ethnic population (David-Beabes et al, 2001;Huang et al, 2008;Sun et al, 2013). However present study reveals significant association when XRCC1 Gln/Gln genotype interact with exposure of wood combustion, exposure of COF and tobacco smoking, while XPD Gln/Gln genotype with betel quid chewing and tobacco smoking.…”
Section: Discussionsupporting
confidence: 93%
“…Most NSCLC cases are diagnosed at advanced stages of the disease, leading to poor five-year survival rate (16% overall survival rate) [2]. In previous studies, we demonstrated that NSCLC risk is present in different ethnic groups [3][4][5][6][7][8]. These data indicate that genetic susceptibility is the most important factor in lung cancer development and contributes to individual lung cancer risk.…”
Section: Introductionmentioning
confidence: 96%